2002
DOI: 10.1002/jmv.10086
|View full text |Cite
|
Sign up to set email alerts
|

Role for mucosal immune responses and cell‐mediated immune functions in protection from airborne challenge with Venezuelan equine encephalitis virus*

Abstract: Venezuelan equine encephalitis virus (VEEV) replicates in lymphoid tissues following peripheral inoculation and a high titre viraemia develops. Encephalitis develops after the virus enters the central nervous system from the blood, with the earliest neuronal involvement being via the olfactory nerve. Following aerosol challenge with virulent VEEV, the virus is thought to replicate in the nasal mucosa and there could be direct entry into the olfactory nerve via infected neuroepithelial cells. Protection from VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Nevertheless, there have been reports that serum antibodies do not always correlate with protection from an aerosol VEEV challenge. For example, in one passive-transfer study, mucosal antibodies were found to be required for the protection of mice from an aerosol challenge (14). In this study, we did not attempt to measure antibodies present in the nasal or respiratory tract; however, our results clearly indicate that i.m.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, there have been reports that serum antibodies do not always correlate with protection from an aerosol VEEV challenge. For example, in one passive-transfer study, mucosal antibodies were found to be required for the protection of mice from an aerosol challenge (14). In this study, we did not attempt to measure antibodies present in the nasal or respiratory tract; however, our results clearly indicate that i.m.…”
Section: Discussionmentioning
confidence: 73%
“…In one study with mice with nonfunctional B cells but normal T-cell activity and cytokine production, complete protection could be achieved only when the passively administered intranasal antibody was accompanied by vaccination with TC-83 (14). The results were interpreted to indicate that the cell-mediated immune responses induced by vaccination with the live-attenuated virus were necessary to achieve protection from aerosol challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The effective dose of post-exposure F5 nIgG, delivered 24 h PI, was 500 µg for SC VEEV infection or 50 µg for aerosol infection (Table 3). Local production of antibody in the CNS or nasal mucosa may also play a role in protection and continued suppression of viral replication due to persistant viral RNA (Charles et al, 1997; Elvin et al, 2002; Griffin, 2010). Although SINV RNA was detected by RT-PCR for 12 months after infection in mice effectively treated with passive antibody (Levine and Griffin, 1992; Levine et al, 1991), we found no detectable viral RNA 14–28 days PI in brain tissue from mice infected by aerosolized VEEV and treated 24 h PI with 50 µg F5 nIgG.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies with MT mice point to the importance of cytokine and T-cell activation (16), and ␣␤ TCR-bearing T cells appear to be required for protection (45). However, protection is not achievable in mouse strains unable to generate an antibody response, such as MT-deficient mice (45).…”
Section: Co-administration Of Cpg Odn With Ad-based Vaccine Does Not mentioning
confidence: 98%
“…This replication-defective vector, based on the ad5 serotype, encodes structural proteins of VEEV (E3-E2-6K). When delivered to BALB/c mice by the intranasal route it was capable of inducing mucosal immunity, which is important in protection against airborne VEEV (16), and is able to elicit protective immunity to mice challenged with airborne VEEV (48).…”
Section: Introductionmentioning
confidence: 99%